INNOVATIVE APPROACHES TO ENHANCING USER SATISFACTION IN HIGHER EDUCATION INFORMATION SYSTEMS - Ameen , Aso K.; Maolood , Ismail Y.; Abdullah , Dana A. (Science Journal of University of Zakho, 2024)
In order to assess how effective information systems are, end-user computing satisfaction (EUCS) is essential. This study evaluates EUCS among 354 employees of the Iraqi Kurdistan Region's (KRI) Ministry of Higher Education and Scientific Research. Through factor analysis, the findings indicate 16-item instrument measuring five core components: content, accuracy, format, ease of use, and timeliness. The results show important patterns and connections, emphasizing how important it is to improve these parts in order to increase user satisfaction. Accuracy had the highest impact on user satisfaction (Standardized Beta = 0.347, p < 0.001), and timeliness were particularly important, while format and ease of use had a direct impact on usability. This study gives useful information for improving IT infrastructure and user support. This will help the Ministry create a better, more efficient, and easier-to-use computer environment that meets the needs and expectations of the workforce. In the end, this will lead to higher productivity and user satisfaction.
Keywords: User Satisfaction; content; accuracy; format; ease of use; timeliness; end-user computing satisfaction; Ministry of Higher Education